MENGAPLIKASIKAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMATIONAL TERHADAP KOMITMEN ORGANISASI: (Study on millennial employees of palm oil processing machinery manufacturing company) - Yulianto; Saryono, Udin (Jurnal Ekonomi STIEP, 2023)
The purpose of this study was to examine the Mediating Role of Job Satisfaction (JS) on the Influence of Transformational Leadership Style (TLS) on Organizational Commitment (OC). The method used is PLS – SEM with a second-order embedded tow stage approach. Data collection techniques used interviews and questionnaires which were distributed to millennial employees who work in palm oil processing machinery manufacturing companies. The tool used to test the research results in this study was SmartPLS 3. The sample for this study was 41 millennial employee respondents. Data were analyzed using path analysis. The results showed that TLS had an effect on JS but had no effect on OC while JS had an influence on OC, and in this study, JS was able to play a mediating role in the relationship between TLS and OC with a significance value of 0.034. and suggestions in this study include increasing the number of samples, and involving personality elements in the testing process and job availability.